DISRUPTED NEURAL NETWORK COMMUNICATION CONTRIBUTES TO DUAL-TASK COST IN FAST-WALKING OLDER ADULTS. (11th November 2018) - Poole, V; Lo, O; Wooten, T; Iloputaife, I; Lipsitz, L; Esterman, M
Abstract: While walking was once thought to be a highly automated process, it has been shown to be increasingly complex, requiring higher-level cognition, with older age. Like other cognitive tasks, walking becomes further complicated with increased cognitive load (e.g., the addition of an unrelated task) and often results in poorer performance (e.g., slower speed). It is not well known, however, how neural network communication relates to this "cost" in performance. The current study investigates the ability of resting-state functional MRI (fMRI) to explain task-related walking speed differences in 57 older adults (21 males; 84 ± 4.4 years) from the MOBILIZE Boston Study cohort. Participants underwent an MRI protocol and completed a gait assessment during two conditions: walking quietly at a preferred pace and while concurrently performing a serial subtraction task. Within and between neural network connectivity measures were calculated from pre-processed fMRI data and were correlated with age-adjusted dual-task cost, the percent change in speed between conditions. Though participants walked relatively fast during the single condition (1.2 ± 0.3 m/s), they were significantly slower during the serial subtraction task (0.95 ± 0.3 m/s; matched pairs t-test=14.4, p<.0001). Among the resting state correlates, higher dual-task costs (slower walking with dual-task) were associated with decreased within motor network connectivity (t=-2.98, p=.004) and connectivity between the ventral attention and executive networks (t=-2.79, p=.007). These findings support the importance of motor network integrity and communication between networks involved in higher-level neurocognitive functioning (e.g., executive function and attention task-switching) to minimize dual-task declines in walking speed.